Visual and Rapid Detection of Escherichia coli O157:H7 in Stool Samples by FTA Card-based Loop-mediated Isothermal Amplification - Fumin Chen; Junyu Wang; Weiguang Li; Yuqian Zhang; Leshan Xiu; Qinqin Hu; Zhengshang Ruan; Ping Chen; Kun Yin (Zoonoses)
Escherichia coli O157:H7 ( E. coli O157:H7) can induce severe diseases in animals and humans that result in significant public health problems. Therefore, the development of rapid and visual detection methods to diagnose E. coli O157:H7 infections and monitor its prevalence is critical for the prevention and control purposes. A colorimetric loop-mediated isothermal amplification (LAMP) assay was utilized to detect E. coli O157:H7. A DNA extraction kit and Flinders Technology Associates (FTA) cards were used to extract nucleic acid in conjunction with colorimetric LAMP detection. The method developed effectively distinguished E. coli O157:H7 from other pathogens with a detection limit of 25 CFU/mL in spiked stool samples. In addition, the nucleic acid of these samples was easily extracted and transported with an FTA card at room temperature. The entire detection process was completed within 35 min using simple constant-temperature equipment. The colorimetric LAMP method with FTA card-based nucleic acid purification was shown to rapidly detect E. coli O157:H7 with sensitivity and specificity. This visual method is expected to be widely used to control E. coli O157:H7 infections, particularly in resource-limited settings.